From humble beginnings to pioneers of resilient farming in Kipkewa Village – The rise of the Langat family farm - Onyango, Polycarp Otieno; Maiyo, Nathan (International Livestock Research Institute, 2025)
Nicholas and Rahab are part of 50 pioneer adaptation farmers that ILRI is working with in two counties to promote farmer-led local solutions to climate change in dairy. The pioneer adaptation farmers share locally developed solutions through farmer-led networks and peer-to-peer learning.